2018
DOI: 10.1007/s11606-018-4393-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Automated Notification on Follow-up of Actionable Tests Pending at Discharge: a Cluster-Randomized Controlled Trial

Abstract: NCT01153451.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Observational studies by Singh et al 32 , 34 and Bhise et al 57 reported a range of between 0.2% and 16.7% failure to follow up test results with the use of an integrated, comprehensive EHR with a test results notification system. A cluster-RCT of an email notification system by Dalal et al reported no significant difference in the rate of documented evidence of follow-up action for test results initially pending at hospital discharge 45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies by Singh et al 32 , 34 and Bhise et al 57 reported a range of between 0.2% and 16.7% failure to follow up test results with the use of an integrated, comprehensive EHR with a test results notification system. A cluster-RCT of an email notification system by Dalal et al reported no significant difference in the rate of documented evidence of follow-up action for test results initially pending at hospital discharge 45 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 studies reported the impact of electronic results management on the rate of missed test results. The majority of the studies in this section were rated as good 30 , 33 , 35 , 48 , 51 , 57 , 59 and fair 29 , 32 , 38–40 , 45 , 47 , 50 , 52 , 66 quality. Of all the studies, 1 was rated as poor quality 34 (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active notification is important for critical results because earlier acknowledgment should lead to more timely action, especially when required follow-up is more urgent. 28,29 When follow-up action is not urgent, as is often the case for Level 3 CSTRs, acknowledgment may not be documented until the action is actually performed (which may be days after the result is finalized). Thus, in theory, the decreased time to acknowledgment that we observed for ANCR may improve time to action for this subset of test results.…”
Section: Discussionmentioning
confidence: 99%
“…In this novel cluster-randomized controlled trial, Dalal and colleagues 3 evaluate the impact of a previously implemented automated email intervention 4 -designed to alert hospital clinicians and primary care providers (PCPs) of actionable TPADs in general medicine and cardiology patients discharged from a tertiary care hospital-on documented action or acknowledgment of actionable TPAD, median time to documented follow-up, and 30-day readmissions. There was no statistically significant difference in the proportion of actionable TPADs with documented action or acknowledgement between the intervention and usual care groups.…”
mentioning
confidence: 99%